Maxillofacial Changes in Melnick-Needles Syndrome - Leilane Larissa Albuquerque do Nascimento; Monica da Consolação Canuto Salgueiro; Mariana Quintela; Victor Perez Teixeira; Ana Carolina Costa Mota; Camila Haddad Leal de Godoy; Sandra Kalil Bussadori (Case Reports in Dentistry)
Background. Melnick-Needles Syndrome is rare congenital hereditary skeletal dysplasia caused by mutations in the FLNA gene, which codifies the protein filamin A. This condition leads to serious skeletal abnormalities, including the stomatognathic region. Case Presentation. This paper describes the case of a 13-year-old girl diagnosed with Melnick-Needles Syndrome presenting with different forms of skeletal dysplasia, such as cranial hyperostosis, short upper limbs, bowed long bones, metaphyseal thickening, genu valgum (knock-knee), shortened distal phalanges, narrow pelvis and shoulders, rib tapering and irregularities, elongation of the vertebrae, kyphoscoliosis, micrognathia, hypoplastic coronoid processes of the mandible, left stylohyoid ligament suggesting ossification, and dental development anomalies. Conclusion. Knowledge of this rare syndrome on the part of dentists is important due to the fact that this condition involves severe abnormalities of the stomatognathic system that cause an impact on the development of the entire face as well as functional and esthetic impairments.